Demography Population of Sumatran Surili (Presbytis melalophos ssp. mitrata Eschsholtz, 1821) and The Diversity of Vegetation as Their Habitat in Riparian Site of Geopark Mengkarang Purba, Merangin Regency - Asrizal Paiman; Novriyanti Novriyanti; Cory Wulan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Surili Sumatera (Presbytis melalophos ssp. mitrata Eschsholtz, 1821) is a primate species commonly found in Sumatra and Kalimantan. Thesubspecies of mitrata are known to be found along the Batanghari River, to the Geopark Mengkarang Purba area. However, data on the number ofspecies in their habitat in Geopark Mengkarang Purba is not yet available. Thus, research on the demographics of riparian populations in riparianareas and the diversity of tree species as a residential habitat in the region is required. The data of this study were collected for ± 3 months in theMerangin Geopark area, West Bangko district in Bedeng Rejo and Rengas Ulu Villages. Geographically this location is located at 0210'43.9